Будова та морфогенез тимусу в постнатальному періоді після внутрішньоутробного введення стафілококового анатоксину та дексаметазону (анатомо-експериментальне дослідження) - Аравіцький, Євген Олегович; Аравицкий, Е. О.; Aravitskiy, E. O. (Запорізький державний медичний університет, 2019)
В результаті роботи було виявлено, що введення дексаметазону призводить до прискореного дозрівання епітеліоретикулоцитів коркової речовини та зменшення кількості малих, середніх, великих лімфоцитів та лімфобластів, PNA+-лімфоцитів в субкапсулярній зоні, корі та мозковій речовині на тлі великої кількості клітин у стадії апоптозу, що також дозволяє краще візуалізувати WGA+-клітини. Також спостерігається затримка процесів позитивної та негативної селекції до періоду компенсаторного відновлення пулу лімфоцитів з їх попередників, що надходять із кісткового мозку. У подальшому це може викликати розвиток імунодефіцитних станів внаслідок порушення морфогенезу вторинних імунних органів. Водночас було виявлено, що вплив стафілококового анатоксину на незрілу імунну систему плода призводить до затримки дозрівання епітеліоретикулоцитів кіркової речовини, що супроводжується зростанням інтенсивності проліферації, а значить і кількості клітин з фігурами мітозів і кількості імунологічно незрілих PNA+- лімфоцитів різного діаметру. Це призводить до змін у процесах внутрішньотимічної міграції, за рахунок чого виникають зміни у відносній площі морфо-функціональних зон тимусу. Також це виявляється у дезорганізації процесів позитивної та негативної селекції, супроводжуючись збільшенням частки незрілих форм лімфоцитів та їх еміграцією із органу на периферію. Як наслідок, виникають зміни у морфогенезі лімфоїдних органів, що може призводити до розвитку алергічної та аутоімунної патології у майбутньому. В результате работы было выявлено, что введение дексаметазона приводит к ускоренному созреванию эпителиоретикулоцитов коркового вещества и уменьшению количества малых, средних, больших лимфоцитов и лимфобластов, PNA+-лимфоцитов в субкапсулярной зоне, коре и мозговом веществе на фоне большого количества клеток в стадии апоптоза, что также позволяет лучше визуализировать WGA+-клетки. Кроме того наблюдается задержка процессов положительной и отрицательной селекции к периоду компенсаторного восстановления пула лимфоцитов из их предшественников, поступающих из костного мозга. В дальнейшем это может вызвать развитие иммунодефицитных состояний вследствие нарушения морфогенеза вторичных иммунных органов. В то же время было обнаружено, что влияние стафилококкового анатоксина на незрелую иммунную систему плода приводит к задержке созревания эпителиоретикулоцитов коры, сопровождающейся ростом интенсивности пролиферации, а значит и количества клеток с фигурами митозов и количества иммунологически незрелых PNA+-лимфоцитов разного диаметра. Это приводит к изменениям в процессах внутритимической миграции, за счет чего возникают изменения в относительной площади морфо-функциональных зон тимуса. Также это проявляется в дезорганизации процессов положительной и отрицательной селекции, сопровождаясь увеличением доли незрелых форм лимфоцитов и их эмиграцией из органа на периферию. Как следствие, возникают изменения в морфогенезе лимфоидных органов, что может приводить к развитию аллергической и аутоиммунной патологии в будущем. The thesis is devoted to the clarification of the peculiarities of the thymus structure and morphogenesis in the postnatal period after intrauterine introduction of staphylococcal anatoxin and dexamethasone with by means of morphometric, histological, lectinhistochemical, immunohistochemical and statistical methods. It was supplemented that after prenatal administration of dexamethasone, a decrease of cortico-medullary ratio by 36% on the 1st day of life was observed, if to compare with the intact animals, mainly due to a decrease in the relative area of the inner cortex (by 44.9%), and up to 30th day this index hadn't reached the reference values. This was accompanied by a decrease in the relative number of small lymphocytes (particularly by 45.9% on the 1st day) and medium lymphocytes (max by 41.7% on the 3rd day) in the cortex, and an increase in the relative number of apoptic lymphocytes (max in 13.5 times on the 1st day) if to compare with intact animals during the first 30 days after birth. In addition, there was an increase in the proportion of large lymphocytes and lymphoblasts of the inner cortex from the 3rd to the 21st day after birth, and an increase in the proportion of lymphocytes in the mitotic phase in the cortex during first 9 days (max on the 3rd day in 3.2 times) in animals after administration of dexamethasone (p <0.05). Also, an increase in the proportion of epitheliocytes in the cortex to the 14th day of life was detected, at max 2.2 times on the 2nd day, in comparison with the reference indexes. It was specified that the prenatal introduction of staphylococcal anatoxin leads to an increase in the relative area of the subcapsular zone by 1.94 times up to the 3rd day of life, and to an increase in the relative area of medulla by 1.2 times from the 3rd day and up to the end of the observed period, if to compare with the intact animals. However, there was an increase in the proportion of small lymphocytes in the subcapsular zone during the first 5 days (max on the 5th day by 20.5%) compared with intact animals. At the same time, there was a decrease in the relative number of small lymphocytes from the 1st to the 9th day in the medulla (max by 14.6% on the 2nd day), compared with the reference values. Also, there was an increase of lymphocytes in the mitosis phase, particularly in the subcapsular zone from day 1 to day 14 (max in 1.7 times on the 1st day), in the inner cortex up to the 3rd day (max in 2.1 times on the 1st day), and in the medulla until the 9th day (max in 2.2 times on the 1st day) compared with the data of the intact animals. An increase in the relative number of epithelial cells in the cortex was observed up to the 3rd day after birth in comparison with the group of intact animals (max by 56.5% on the 3rd day), (p <0.05). It's been shown that prenatal administration of dexamethasone results in an increase of receptor expression for lentil lectin and the number of LCA+-dendritic cells on day 5–14, with a max increase by 51.3% at day 5, compared to the reference values. However, more intense expression of β-D-galactose receptor shielded with sialic acid was detected from the 14th to 30th day of life (++) in the medulla, compared with the intact animals (+). On the contrary, the number of WGA+-epitheliocytes was lower by 19.2% on the 30rd day in cortex and by 24.2% on the 14th day in medulla, if to compare with the reference group. There was also a decrease in the rate of benzidine label accumulation to β-D-galactose (+) in the cortex and medulla during the first 2 days, compared to the intact group (++). It's been proved that after prenatal introduction of staphylococcal toxoid there was a more intensive accumulation of the benzidine label to the lentil lectin from the 3rd to the 9th day, and the amount of LCA+-dendritic cells is bigger during the first 3 days with a max increase by 58.8% on the 2nd day in comparison with reference indexes. In addition, there was an increase in the number of WGA+-epithelial cells in the thymic cortex and medulla during the first 3 days and on the 30th day of postnatal life, accompanied by more intensive expression of receptors to N-acetyl-D-glucosamine during first 9 days of the postnatal period in cortex (+++) and during 3–5 days of life in the medulla (+++), compared with expression level (++) in intact animals. Also, from the 9th to the 30th day in the medulla a more intensive expression of receptors to ricinic lectin (++) was detected, compared to the intact group (+). At the same time, more intensive accumulation of the benzindine mark on immature PNA+-lymphocytes during the first 3 days of postnatal life in cortex and medulla was noted, and a greater difference in the intensity of expression was observed in the cortex, if to compare with the reference group (+++ vs + in accordance). It was established that administration of dexamethasone to rats in the antenatal period leads to a decrease in the intensity of expression of cytokeratins 5/14 receptors during the first 2 weeks of life and to a progressive decrease in the area occupied by CK 5/14+-epitheliocytes throughout the observation period (on the 1st day relative area of CK 5/14+-cells is by 33.1% less, and by the 30th day it is by 63.5% less) compared to the intact group of animals. It was found that in the group of antigen-primed animals there was an increase in the expression of cytokeratins 5/14 receptors during the all period of observation with a maximum in the first 3 days, and the specific area occupied by CK 5/14+-epitheliocytes was bigger during first 9 days after birth (particularly by 59.1% on the 1st day), if to compare with intact group of animals.
Строение и морфогенез тимуса в постнатальном периоде после внутриутробного введения стафилококкового анатоксина и дексаметазона (анатомо-экспериментальное исследование)
Structure and morphogenesis of thymus in the postnatal period after prenatal introduction of staphylococcal anatoxin and dexamethasone (anatomical experimental research)
Keywords: тимус; дексаметазон; стафілококовий анатоксин; коркова речовина; мозкова речовина; лімфоцити; епітеліоретикулоцити; лектини PNA; WGA; LCA; RCA; цитокератини 5/14; стафилококковый анатоксин; корковое вещество; мозговое вещество; лимфоциты; эпителиоретикулоциты; лектины PNA; цитокератины 5/14; thymus morphogenesis; dexamethasone; staphylococcal anatoxin; thymic cortex; thymic medulla; lymphocytes; epithelioreticulocytes; RCA lectins; cytokeratin 5/14